Clinical study of acute intestinal obstruction in tertiary care centre - Daddenavar, Vikas M.; Mirji, Pramod; Kalburgi, Ishwar (International Surgery Journal, 2017)
Background: Acute intestinal obstruction is one of common abdominal emergencies and is associated with significant morbidity and mortality, especially if it progresses to bowel ischemia. The aim of this study is to analyse various modes of presentation of acute intestinal obstruction in both children and adult age group, etiopathogenesis, various therapeutic modalities of treatment and to accomplish operative management and anticipate the post-operative complication. Methods: Fifty consecutive patients of all age groups presenting with acute intestinal obstruction were admitted in SN Medical College HSK hospital were taken randomly and managed between February 2013 to February 2016. A detailed examination was done as per proforma after admission. Plain X-ray erect abdomen was done in all cases except inguinal hernias with obstruction. Results: Mean age distribution was 35.4 years. Incidence in male was more compared to female. Pain abdomen was found in 39 (78%), vomiting in 35 (70%), distension abdomen in 29 (58%) and constipation in 26 (52%) patients as main complaint. Commonest cause was postoperative adhesions. Mean duration of stay in hospital was between 1-5 weeks (average 2 weeks). Conclusions: All age groups were involved. More commonly found in males than females. Main complaint was pain abdomen followed by vomiting, distension and constipation. Plain X-ray abdomen and ultrasonography were important. Pathology ranged from simple bands to malignant obstruction. Postoperative adhesions were the commonest cause of obstruction. Earlier the presentation better the outcome was found.